The European Community, the European Union and the International law of treaties - Verwey, Delano (T.M.C. Asser Press, 2004)
Provides a comparative legal analysis of the European Community and the European Union's external treaty-making practice. This book will be of interest to practitioners in EU law, international law and the law of international organisations as well as to specialists who work for the Foreign Office and within international organisations.